Pola Spasial Kriminalitas Narkoba di Kota Kendari - Arif Rahman; Bahtiar Bahtiar; Oheo K. Haris (Universitas Halu Oleo, 2021)
The development of narcotics in Kendari City has spread to ten sub-districts. The purpose of this research is (1) for analyzing the spatial pattern of drug crime in Kendari City, (2) for analyze the factors causing drug crime in Kendari City; (3) for analyze the factors causing drug crime in Kendari City. The analytical method used in this research is spatial analysis and qualitative descriptive analysis. The results of the study show (1) The spatial pattern of drug crime in Kendari City spreads across ten sub-districts in Kendari City which tends to cluster. 2) Hypothesis testing states that the infrastructure development program the factors causing drug crime in Kendari City are depression factors, economic factors, education factors, trial and error factors, environmental factors, dependency factors, family factors; and (3) Efforts to overcome narcotics abuse of drug crime in Kendari City are Pre-Emtif Efforts, namely (a) Increasing self-confidence in God Almighty, (b) Providing correct and intensive information, (c) Encouraging the creation of alternative community livelihoods . Preventive Efforts are (a) Conducting Counseling on the Dangers of Narcotics Abuse, (b) Conducting Community Disease Operations (Operation Concentrated), (c) City Government Efforts. Repressive efforts are conducting investigations and investigations of perpetrators of narcotics abuse crimes. Persuasive Efforts are to provide encouragement for anti-drug villages where some of these areas are the most frequent criminal acts of narcotics abuse, curative (treatment), rehabilitative (rehabilitation), and socialization. Keywords: Spatial Pattern, Criminal, DrugsPerkembangan narkotika di Kota Kendari menyebar ke sepuluh kecamatan. Tujuan dari penelitian ini yaitu (1) menganalisis pola spasial krimalitas narkoba di Kota Kendari, (2) menganalisis faktor penyebab tindak kriminalitas narkoba di Kota Kendari; dan (3) menganalisis upaya penanggulangan penyalahgunaan narkotika kriminalitas narkoba di Kota Kendari. Analisis data yang digunakan dalam penelitian ini adalah analisis spasial dan analisis deskriptif kualitatif. Hasil penelitian menunjukan (1) Pola spasial krimalitas narkoba di Kota Kendari menyebar disepuluh kecamatan di Kota Kendari yang cenderung mengelompok. 2) Pengujian hipotesis menyatakan bahwa program pengembangan infrastruktur faktor penyebab tindak kriminalitas narkoba di Kota Kendari adalah faktor depresi, faktor ekonomi, faktor pendidikan, faktor coba-coba, faktor lingkungan, faktor ketergantungan, faktor keluarga; dan (3) Upaya penanggulangan penyalahgunaan narkotika kriminalitas narkoba di Kota Kendari adalah Upaya Pre - Emtif yaitu (a) Meningkatkan keimanan diri terhadap Tuhan Yang Maha Esa, (b) Memberikan informasi yang benar dan intensif, (c) Mendorong terciptanya alternative mata pencaharian masyarakat. Upaya Preventif yaitu (a) Mengadakan Penyuluhan mengenai Bahaya Tindak Pidana Penyalahgunaan Narkotika, (b) Mengadakan Operasi Penyakit Masyarakat (Operasi Pekat), (c) Usaha Pemerintah Kota. Upaya Represif yaitu melakukan penyelidikan dan penyidikan terhadap pelaku tindak pidana penyalahgunaan narkotika. Upaya Persuasif yaitu memberikan dorongan bagi kampung anti narkoba yang mana beberapa wilayah tersebut paling sering terjadi tindak pidana penyalahgunaan narkotika, Kuratif (pengobatan), Rehabilitatif (rehabilitas), serta sosialisasi. Kata Kunci : Pola Spasial, Kriminalitis, Narkoba